Detection of Significant Association Between Variants in Cannabinoid Receptor 1 Gene (CNR1) and Personality in African–American Population - Yao, Yinghao; Xu, Yi; Zhao, Junsheng; Ma, Yunlong; Su, Kunkai; Yuan, Wenji; Ma, Jennie Z.; Payne, Thomas J.; Li, Ming D. (Frontiers in Genetics, 2018)
Background: Several studies have revealed significant associations between single nucleotide polymorphisms (SNPs) in the cannabinoid receptor 1 (CNR1) gene and a broad spectrum of psychiatric disorders such as major depressive disorder (MDD), attention deficit hyperactivity disorder (ADHD), and schizophrenia. Personality traits that are highly related to susceptibility to these conditions have been associated with the CNR1 variants in subjects of Caucasian origin. However, there are no reported studies regarding the effects of CNR1 polymorphisms on personality traits in the African-American (AA) population. Methods: We performed an imputation-based association analysis for 26 CNR1 variants with five dimensions of personality in 3,046 AAs. Results: SNPs rs806372 and rs2180619 showed a significant association with extraversion after Bonferroni correction for multiple testing (p < 0.0019). Further, several extraversion-associated SNPs were significantly associated with conscientiousness, agreeableness, and openness. SNP priority score analysis indicated that SNPs rs806368, rs806371, and rs2180619 play a role in the modulation of personality and psychiatric conditions. Conclusion: CNR1 is important in determining personality traits in the AA population.